2007
DOI: 10.1128/jvi.01506-07
|View full text |Cite
|
Sign up to set email alerts
|

Localization and Membrane Topology of Coronavirus Nonstructural Protein 4: Involvement of the Early Secretory Pathway in Replication

Abstract: The coronavirus nonstructural proteins (nsp's) derived from the replicase polyproteins collectively constitute the viral replication complexes, which are anchored to double-membrane vesicles. Little is known about the biogenesis of these complexes, the membrane anchoring of which is probably mediated by nsp3, nsp4, and nsp6, as they contain several putative transmembrane domains. As a first step to getting more insight into the formation of the coronavirus replication complex, the membrane topology, processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
214
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(241 citation statements)
references
References 76 publications
(93 reference statements)
18
214
0
1
Order By: Relevance
“…Second, BFA-mediated deactivation of Arf1 that disables the COPI activity inhibits the replication of BFA-sensitive viruses (30,41,52). Finally, the expression of the Sar1 mutant blocks the replication of a coronovirus (45). In this study, the inhibition of virus accumulation was paralleled by the disruption of the 6K vesicles, and the ERES was the putative site where the 6K vesicles originated and developed.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Second, BFA-mediated deactivation of Arf1 that disables the COPI activity inhibits the replication of BFA-sensitive viruses (30,41,52). Finally, the expression of the Sar1 mutant blocks the replication of a coronovirus (45). In this study, the inhibition of virus accumulation was paralleled by the disruption of the 6K vesicles, and the ERES was the putative site where the 6K vesicles originated and developed.…”
Section: Discussionmentioning
confidence: 72%
“…The 3A protein is a small membrane protein with multiple functions in the viral life cycle and was shown to localize to the ERES in Buffalo green monkey kidney cells (77). Similarly, the replication of a coronovirus is inhibited in murine LR7 cells expressing a dominant mutant of Sar1 that disables the COPII-associated ER export machinery (45). However, in both cases, it is not clear if the COPII complex is involved in the biogenesis of the induced membranous vesicles.…”
Section: Discussionmentioning
confidence: 95%
“…The transmembrane domain is inserted into the endoplasmic reticulum (ER) membrane co-translationally and plays an important scaffolding role for the replication transcription complex [9]. Recently, it was shown that three transmembrane domains were predicted for the SARS-CoV nsp 3 but only two were found to span the ER membrane orienting the protease domain of nsp 3 on the cytoplasmic side where viral replication occurs [13,15]. In murine hepatitis virus (MHV), five transmembrane domains were predicted but only two domains were found to span the membrane, also locating the protease domain on the cytoplasm side [13,15].…”
Section: Discussionmentioning
confidence: 99%
“…The Mpro contained within nsp 5 cleaves nsps 5 through 16. The biological characteristics of many nsps have been previously reported [9,10,[12][13][14][15][16][17]. In addition to nsps 3 and 5, which contain proteases PL2 and Mpro, respectively, nsps 2, 4, and 6 contain hydrophobic residues predicted to play a role in anchoring the RTC to the Golgi.…”
Section: Introductionmentioning
confidence: 92%
“…4A). N glycosylation at N-X-C sites is uncommon but was first discovered in synthetic peptides, where the motif could act as an N-glycan acceptor (5), and was subsequently identified in several viral and cellular glycoproteins (28,32,41,44,45). Using H 7ko , we generated additional mutant proteins lacking N19 and N152 alone or in combination (H 9ko ), ultimately resulting in complete removal of all potential N-glycosylation sites (Fig.…”
Section: Resultsmentioning
confidence: 99%